(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The prevalence of dental caries in childhood is one of the problems related to children’s oral health. The aim of this study was to determine the risk of caries in children aged 6-12 years based on parental information and its relationship with BMI and DMFT in Ahvaz. Methods and materials: The necessary permits were obtained from the Ahvaz Education Department, and then 300 samples of the city’s primary schools were selected. Students were examined with a disposable dental mirror and the number of decayed, missed, and restored permanent and deciduous teeth was recorded in the DMFT table. After that, the questionnaire was completed with the help of parents. The validity of this questionnaire was confirmed by 5 pediatric dentists and the reliability of this questionnaire was confirmed by conducting a pilot study on 10 children based on Cornbach coefficient of 0.85. Results: Maternal occupation was associated with moderate caries risk (p = 0.007). Economic situation was associated with low risk (p = 0.0001). The mean weight of the child in the high risk group was significantly higher than the low risk groups (p <0.001) and medium risk (p <0.001). The mean DMFT in the low risk group was significantly lower than the medium risk (p <0.001) and high risk groups (p <0.001). The mean BMI in the high risk group was significantly higher than the medium risk groups (p <0.001) and low risk (p <0.001). Conclusion: Economic status, mother’s job and child’s weight are associated with caries risk. Also, DMFT and BMI index have a direct and significant relationship with the risk of caries.